2010
DOI: 10.1080/10888700903583459
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Exercise Pen Use by Circus Tigers (Pathera tigris tigris)

Abstract: This study quantified the behavior of 11 tigers during periodic access to an exercise pen throughout the day and night. The study determined the amount of time spent in the pen and the percentage of time spent performing stereotypic pacing, normal locomotor behavior, and lying down while in the pen. Average access to the exercise pen was 10 hr 49 min overnight and 5 hr 30 min during the day. At night, the tigers spent 29.1% of their time in the exercise pen, during which they paced 19.6% and performed normal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Similar levels of stereotypical pacing have been identified in both zoos (23%) and circuses (20%), indicating that both forms of captivity often provide a sub-optimal environment [37,53]. However, Biolatti et al [32] recorded captive tiger activity budgets to show sleeping (32.64%), resting (27.50%), and walking (17.30%).…”
Section: Mental Statementioning
confidence: 74%
See 1 more Smart Citation
“…Similar levels of stereotypical pacing have been identified in both zoos (23%) and circuses (20%), indicating that both forms of captivity often provide a sub-optimal environment [37,53]. However, Biolatti et al [32] recorded captive tiger activity budgets to show sleeping (32.64%), resting (27.50%), and walking (17.30%).…”
Section: Mental Statementioning
confidence: 74%
“…Whilst circuses can offer positive goal-directed rewards through training [61], there is clear evidence in the scientific literature of stereotypical pacing in tigers kept in captivity, including within circuses [18,19,34,37,42,51,53,57,62]. The literature also suggests that age and sex can impact on individual mental state.…”
Section: Mental Statementioning
confidence: 99%
“…Kiley-Worthington [ 9 ] has a description of early exercise pens used in England in 1990. Krawczel et al [ 10 ], Nevill and Friend [ 11 ], and Nevill et al [ 12 ] further reported on the utilization of exercise pens by circus tigers.…”
Section: Methodsmentioning
confidence: 99%
“…De tijger wordt gehouden in dierentuinen, safariparken, circussen en in tijger boerderijen (Nevill et al 2010;Abbott en Van Kooten 2011;Liu et al 2015). In tijger boerderijen worden tijgers gefokt om de soort in stand te houden en als attractie voor toeristen (Kirkpatrick en Emerton 2010).…”
Section: Tijger (Panthera Tigris)unclassified